New Hybrid Quick Response Manufacturing Framework To Improve Delivery Performance At Engineer-To-Order Company - Bong, Cheng Siong (2019)
The competitiveness and growth of the small and medium enterprises (SMEs) is critical for the Malaysian economy. In the last few years amidst the volatile external environment and escalating global competition, SMEs have witnessed a marked improvement in their performance. Malaysian SMEs are expected to contribute 42% to the country’s gross domestic product (GDP) by 2020, remain as an important economic agent to transition the economy to a developed nation in the years to come. As such, productivity of SMEs is imperative to ensure the competitiveness of manufacturing organization in the country. The present scenario reveals that most SMEs supply custom engineered products are confronted with various challenges in retaining their competitive advantages in the global market. Hence, selecting the best practices that associated to their competitive priorities will help the company outperforms their competitors in the long term. However, many failed to do so due to their rush to emulate the success of their counterparts. This research study has set out for an engineer-to-order (ETO) manufacturing company that experiences poor on-time delivery (OTD) performance of about 54%. The aim of the study was to reduce the lead time and hence improve OTD to customers by designing a new hybrid Quick Response Manufacturing (QRM) framework in the organization. The objectives and methodologies include designing a QRM based material flow system controlled by capacity utilization to ease the overloading in the production. A simulation base model was built and validated followed by experimentations of capacity utilization based control (UBC) system. The deciding factors such as throughput (TP), work-in-process (WIP) and average manufacturing critical-path time (MCT) per job were analysed and compared. To address the limitations of QRM, the second phase is designing a system integrated with Lean and TQM practices to eliminate office wastes and to cultivate concept of self-assessment respectively. This hybrid QRM was also meant to create a balance and sustainability in the long run. The last phase is engaging a case company to validate the developed hybrid system in the real-life environment. Simulation results showed that UBC system performed better than the current cost based production in the case company. The achievement of the objectives predetermined above include WIP and MCT reduced by 30% and 18% respectively, resulting improvement of OTD from 54% to 75%. This has led to the economic impacts particularly with respect to TP and sales increased by 31% and 69% respectively after the deployment of the new system in the case company. The thesis identifies issues arising from the application of hybrid QRM in the job shops which have implications for industry practices. It concludes by outlining further research that can be undertaken in the emerging trend of Industry 4.0.